The Anti-Semitic Disturbances on Corfu and Zakynthos in 1891 and their Socio-political Consequences - Liata, Eftychia (The Historical Review/La Revue Historique, 2008)
The text below is a summary of my book Η Κέρκυρα και η Ζάκυνθος στον κυκλώνα του αντισημιτισμού. Η συκοφαντία για το αίμα του 1891 [Corfu and Zakynthos in a tornado of anti-Semitism: the ghezera of 1891], published in 2006 by the Institute for Neohellenic Research / NHRF, on the subject of the anti-Semitic incidents that broke out in the Spring of 1891 on those two Ionian Islands. Based on hitherto unknown archival material (public documents, diary entries, private texts) and press publications of the day, while at the same time making use of the scarce available bibliography, this study endeavours to reconstruct the events in the light of fresh data, pose questions and propose answers for the causes and the mechanisms leading to the aggravation of the situation, the outbreak of violence and the multifaceted consequences thereof, not only on the local but also the national level. The study also records the depiction of the events through contemporary and subsequent works of historiography, as well as their recasting in Greek literature to this day.